Book Review: Craft Sciences by Tina Westerlund et al (eds) - Duncan Berryman (EXARC Journal)
This book sets out to bring the topics of craft science and practitioner-research to a wider audience and integrate them into current craft practices. This is a subject that has seen significant development in Scandinavia but is much less common in other parts of Europe. The essays gathered here present case studies from a range of different crafts, from woodworking and pottery to gardening and textile production. Each essay presents a different approach to how practitioner-researchers can document their craft practices, enabling them to be recorded and passed on to others.